Kemandirian Belajar dan Kemampuan Pemecahan Masalah pada Mahasiswa - Dewi, Ratna Sari; Puriani, Risma Anita (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2023)
This study was based on the phenomenon of the presence of students who were so afraid to express their opinions and who copied task in the execution of independent tasks friend as one indication of the lack of independent learning. It was thought to have an influence on problem solving skills in students. The purposes of research were to describe the correlation between independent learning with problem solving skills. This research used quantitative research correlational techniques. The subjects were the students of Guidance and Counseling Education Faculty of Sriwijaya University with a sample of 105 students from the population of 145 students. The sample was selected by proportional random sampling technique. The instrument used in this study was Likert scale models with reability as big as 0.916 (independent learning), and 0.923 (problem solving skills). Data analyzed using descriptive statistics, product moment correlation.The study revealed that: (1) there was a significant correlation between academic self-concept and problem solving skills (r= 0,590), (2) there was a significant correlation between the independent learning and problem solving skills (r= 0,601), (3) there was a significant correlation between academic self-concept and independent learning with problem solving skills (R= 0,716). The research’s implications to guidance and counseling are used as a input to create a guidance and counseling service programs.